Simple Evidentiary in Bankruptcy Cases - Marwanto, Marwanto; Murni, R.A. Retno; Yogantara S, Pande (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 4 (2022), 2022)
This study aims to find and analyze the concept of simple evidentiary in bankruptcy cases and to find and analyze the characteristics of simple evidentiary in bankruptcy cases. This research is a type of normative legal research using a statutory approach and a conceptual approach. The results showed that the simple concept of proof in bankruptcy cases is not the whole proving process in the bankruptcy case trial process, but only simply proving of the existence of the debt. However, if it turns out that at trial there are difficulties in proving the three facts mentioned above, then it is certain that the proof is not simple. In bankruptcy cases, the trial process is carried out with simple evidentiary intended so that this case can be resolved quickly and effectively. Quick because the settlement of bankruptcy cases in the commercial court has determined the time period at each level of the judiciary. Effective because the decision on the bankruptcy petition case is instantaneous.